Biodegradation of low-density polyethylene and polystyrene in superworms, larvae of Zophobas atratus (Coleoptera: Tenebrionidae): Broad and limited extent depolymerization. (November 2020) - Peng, Bo-Yu; Li, Yiran; Fan, Rui; Chen, Zhibin; Chen, Jiabin; Brandon, Anja M.; Criddle, Craig S.; Zhang, Yalei; Wu, Wei-Min
Abstract: Larvae of Zophobas atratus (synonym as Z. morio, or Z. rugipes Kirsch, Coleoptera: Tenebrionidae) are capable of eating foams of expanded polystyrene (EPS) and low-density polyethylene (LDPE), similar to larvae of Tenebrio molitor . We evaluated biodegradation of EPS and LDPE in the larvae from Guangzhou, China (strain G) and Marion, Illinois, U.S. (strain M) at 25 °C. Within 33 days, strain G larvae ingested respective LDPE and PS foams as their sole diet with respective consumption rates of 58.7 ± 1.8 mg and 61.5 ± 1.6 mg 100 larvae −1 d −1 . Meanwhile, strain M required co-diet (bran or cabbage) with respective consumption rates of 57.1 ± 2.5 mg and 30.3 ± 7.7 mg 100 larvae −1 d −1 . Fourier transform infrared spectroscopy, proton nuclear magnetic resonance, and thermal gravimetric analyses indicated oxidation and biodegradation of LDPE and EPS in the two strains. Gel permeation chromatography analysis revealed that strain G performed broad depolymerization of EPS, i.e., both weight-average molecular weight (Mw ) and number-average molecular weight (Mn ) of residual polymers decreased, while strain M performed limited extent depolymerization, i.e., Mw and Mn increased. However, both strains performed limited extent depolymerization of LDPE. After feeding antibiotic gentamicin, gut microbes were suppressed, and Mw and Mn of residual LDPE and EPS in frass were basically unchanged, implying a dependence on gut microbes for depolymerization/biodegradation. Our discoveries indicate that gut microbe-dependent LDPE and EPS biodegradation is present within Z. atratus in Tenebrionidae, but that the limited extent depolymerization pattern resulted in undigested polymers with high molecular weights in egested frass. Graphical abstract: Image 1 Highlights: Zophobas atratus eat low-density polyethylene (LDPE) and expanded polystyrene (EPS) foams. Larvae from two sources biodegraded LDPE via limited extent depolymerization. Larvae from different sources biodegraded EPS via broad or limited extent depolymerization. Antibiotics inhibited depolymerization of LDPE and EPS, indicating gut-microbial dependence. Abstract : Major findings are that first demonstrated depolymerization/biodegradation of LDPE and confirmed biodegradation of EPS in Zophobas atratus larvae from two different sources; verified gut-microbe dependent LDPE and EPS degradation; and discovered two different depolymerization patterns during plastic biodegradation.